Effect of Remimazolam- Vs Propofol-Based Intravenous Anesthesia on Surgical Stress Response and Post-Operative Immune Function in Patients with Gastric Radical Surgery - Xu Q; Cheng X; Sun H; Su G; Fei Y; Wang C; Han C (Dove Medical Press, 2024)
Qingqing Xu, Xue Cheng, Hong Sun, Guangyuan Su, Yuanhui Fei, Chunhui Wang, Chao Han Department of Anesthesiology, The Affiliated Yixing Hospital of Jiangsu University, Yixing, Jiangsu, People's Republic of ChinaCorrespondence: Chao Han, Department of Anesthesiology, The Affiliated Yixing Hospital of Jiangsu University, Yixing, Jiangsu, 214200, People's Republic of China, Tel +8613961568178, Email staff940@yxph.comPurpose: This study aimed to compare the impact of remimazolam-based versus propofol-based intravenous anesthesia on surgical stress and post-operative immune function in patients undergoing gastric radical surgery.Patients and Methods: Sixty-eight patients aged 50 to 80 undergoing gastric radical surgery were randomly assigned to the remimazolam group (group R) or the propofol group (group P), receiving remimazolam or propofol-based intravenous anesthesia, respectively. The primary outcome measured was peri-operative serum stress indicators and lymphocyte subtypes. Secondary outcomes included hemodynamic vitals, recovery quality, postoperative pain profiles and potential adverse effects.Results: The demographic and surgical characteristics of the 60 analyzed patients were comparable. The absolute counts of CD3+CD4+ and CD3+CD8+ cell decreased significantly on POD1 compared with baseline. On POD3, the numbers of CD3+CD4+ cells in group R were lower than baseline and Group P, whereas the CD3+CD8+ cell counts in both groups were lower than baseline, with group R higher than group P. The CD3-CD16+CD56+ cell numbers in both groups on POD1 and POD3 decreased significantly compared to baseline with group P lower than group R on POD3. The serum levels of IL-1β, IL-6, TNF-α, ACTH and COR rose sharply 2 hours after the beginning of surgery compared to baseline. Notably, all these parameters in group R were higher than those in group P. Additionally, blood pressure and intra-operative vasoactive drug frequency in group R were higher than that in group P. No significant differences in recovery quality, postoperative pain profiles, and potential adverse effects were observed.Conclusion: Remimazolam-based intravenous anesthesia might favour the recovery of cellular immune function in early postoperative period compared to propofol. On the contrary, remimazolam was inferior to propofol in suppressing surgical stress. Further studies with larger sample sizes are needed to confirm our findings.Keywords: remimazolam, propofol, surgical stress, post-operative immune function, gastric radical surgery